Social Support and its Relation with Daily Activities among Elderly People of Yazd - Tahere Soltani; Seid Saied Mazloomymahmmodabad; Mohammad Ali Morowatisharifabad; Hossein Fallahzadeh; Abdolkhalegh Jafari (Shahid Sadoughi University of Medical Sciences, 2015)
Introduction: Aging priod is Special features and many problems in all dimensions of human life and cause increased supportive needs. During recent years the rapid increase in the senior population, their disabilities, reduced independence, and increased dependence have drawn more attention toward issues related to social support in this group. Social support impacts different dimensions of health of the elderly population. Therefore, The aim of this study was to determine the social support and activities of daily living of elderly is Yazd. Materials and Methods: This study was a cross-sectional study was conducted on 265 elderly people in the city of Yazd. A cluster sampling was random. The data are composed of items demographic and "Activities of daily living" questionnaire "social support Phillips". then using the software SPSS 16 analysis were with statistical tests of Kruskal-Wallis, Mann-Whitney, Spearman correlation and crosstabs . Results: The results showed that the average total social support in the elderly (19/84±3/43) of the range acquisition score was (0-23). The results also indicate that between social support and age, type of housing, and activities of daily living, there was a statistically significant , negative direct solidarity between social support and age were observed , there was a statistically significant, positive direct solidarity between social support and activities of daily living were observed. Discussion & Conclusion: According to the results of this study, increased social support in performing activities of daily living and health promotion can be effective in elderly .Therefore enhance social support and protection needs of the elderly should expand their networks of support for elderly.